Co-production in action: perceiving power in the organisational dimensions of a global biodiversity expert process - Montana, J (Springer, 2019)
Opening up knowledge–action systems to a wider range of disciplinary and societal actors is considered to be a necessary step in achieving transformative change for sustainability. In science for sustainability, there is a growing body of experience and literature of putting this ‘co-production’ into action. However, there is an opportunity to strengthen the application of analytical resources for more explicitly recognising and accounting for the power relations embedded in these initiatives. This paper deploys social theory from science and technology studies to develop an approach to perceive power relations between the participants, processes and products of co-production. This necessitates paying attention to the multiple and distributed organisational spaces where co-production takes place to discern: who participates; who (and what) is represented; how deliberations are structured; and how outcomes are circulated. This paper shows that these organisational dimensions of participation, representation, deliberation, and circulation not only give structure to co-productive forums, but can also define the power relations between their participants, processes and products. The paper then illustrates the applicability of this approach using the case of a current global expert process for biodiversity: The Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES). This case study offers insights on the challenges and opportunities for designing and evaluating co-production initiatives for sustainability.